Synthesis and Characterization of Nickel(II) Complexes of Various Substituted Acid Hydrazides - Adekunle, F.A.; Woods, J.A.O.; Onawumi, O.O.E.; Odunola, O.A. (Asian Journal of Chemistry, 2010)
Complexes of nickel(II) with m-chloro benzoic acid, p-amino benzoic acid and nicotinic acid hydrazides as ligands have been synthesized in ethanolic medium. They were characterized by elemental analyses, infrared, diffuse electronic reflectance spectroscopy and room temperature magnetic susceptibility measurements. The complexes are generally insoluble in common solvents. The results suggest octahedral coordination in which the nickel(II) is bonded to the ligands using the amide carbonyl and the amino nitrogen of the hydrazide moiety. The complexes exhibited varied antimicrobial activities against some tested organisms.